Redefining Inclusion in AI’s Digital Economy: Women’s Entrepreneurship as a Catalyst for Ethical and Equitable Healthcare Innovation - Bhatt, Girish Chandra; Gopaliya, Manoj Kumar; Bhatt, Kartikey (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The convergence of artificial intelligence (AI) and digital entrepreneurship is revolutionizing the delivery of healthcare around the world. Yet a key strategy blind spot persists, and that is the gender gap in digital participation and entrepreneurial leadership. This paper positions women’s entrepreneurial empowerment as a central mechanism to accelerate ethical and equitable innovation in healthcare. Through a literature review of peer-reviewed articles, global policy frameworks, and a review of relevant empirical case studies (2015–2025), this paper creates a conceptual model linking inclusive leadership, ethics-by-design, stakeholder co-creation, and policy ecosystems. This analysis concludes that women-led ventures in health tech are more aligned with public interest values, such as trust, transparency, and social responsiveness. This paper concludes with practical recommendations for policymakers, investors, and ecosystem builders to include equity as infrastructure, not as accessory, in the future of healthcare innovation.